IMPLEMENTASI SAFETY INDUCTION DALAM MENINGKATKAN KESELAMATAN KERJA DI PT CONTEMPORARY AMPEREX TECHNOLOGY LIMITED ENERGY ENGINEERING (PT CCIEE) - Widhiantika, Wieke; Darmawan, Wendi; Kartika, Iin Ira; Jumaedi, Jumaedi; Fitriyastanti, Devi; Triyuliana, Chaerani; Azhari, Yasin; Mulyana, Putri Gustina (Jurnal Kesehatan dan Kedokteran, 2025)
The increasing activities in the construction and energy industries have raised the risk of occupational accidents, making OHS implementation essential. Objective: This study aims to analyze the procedures and importance of safety induction in improving workplace safety at PT CCIEE. Method: This research used a descriptive qualitative method with a field study approach through observation, documentation, and literature review, analyzed through data reduction, data presentation, and conclusion drawing. Findings: The findings show that safety induction was implemented through OHS policy delivery, workplace hazard identification, PPE use, emergency procedures, and supporting activities such as toolbox meetings, general safety talks, and safety patrols. These practices improved workers’ understanding, awareness, and compliance with workplace safety procedures. Implication: This study indicates that safety induction is not merely an administrative procedure but a preventive strategy to develop a workplace safety culture. Originality: The originality of this study lies in its focus on safety induction implementation in construction and energy companies in Indonesia, which remains limited in previous studies.